JOURNAL OF POSTGRADUATE MEDICAL INSTITUTE: ANALYSIS THROUGH BIBLIOMETRIC LENS - Jan, Muhammad Yahya; Ullah, Saeed; Jan, Saeed Ullah; Jan, Tahir; Ahmad, Hafiz Nafees (Journal of Postgraduate Medical Institute, 2021)
Objective: To analyze the publication patterns of Journal of Postgraduate Medical Institute (JPMI) over a period of 32 years. Methodology: Bibliometric technique was used to evaluate original articles, review articles and case reports published in JPMI from 1986 to 2018. Publication patterns were analysed with regards to number of published articles per year, their specialty wise distribution and geographical distribution. Citations pattern was also noted. Results: A total of 1671 articles were published in JPMI in a time span of 32 years. The year 2004 was recorded as the most productive year with 113 publications. Khyber Pakhtunkhwa (KP) province was the most contributing geographic zone (n=4614, 79.94%). The subject of surgery (n=205, 12.58%) followed by medicine (n=198, 12.15%) were the most frequent subjects of research. Journals (n=29400, 90.03%) followed by books (n=2035, 6.23%) were cited more in all publications. Five pages articles were larger in number. The female contribution was one-fifth of the total. Conclusion: The study concluded that the subjects of surgery and medicine were more published and majority of the authors that contributed in the published articles were from KP.